Managing Human Resources - F. Cascio Wayne (New York : MC Graw Hill, 2010)
Wayne Cascio's Managing Human Resources, 8e is perfect for the general management student whose job inevitably will involve responsibility for managing people. It explicitly links the relationship between productivity, quality of work life, and profits to various human resource management activities and as such, strengthens the students' perception of human resource management as an important function, which affects individuals, organizations, and society. It is research-based and contains strong links to the applicability of this research to real business situations.
Keywords: Personnel management; Managing Human Resources